State-Dependent Modulation of Gap Junction Signaling by the Persistent Sodium Current - Haas, Julie S.; Landisman, Carole E. (Frontiers in Cellular Neuroscience, 2012)
Thalamic neurons fluctuate between two states: a hyperpolarized state associated with burst firing and sleep spindles, and a depolarized state associated with tonic firing and rapid, reliable information transmission between the sensory periphery and cortex. The thalamic reticular nucleus (TRN) plays a central role in thalamocortical processing by providing feed-forward and feedback inhibition to thalamic relay cells; TRN cells participate in the generation of sleep spindles, and have been suggested to focus the neural “searchlight” of attention. The mechanisms underlying synchrony in the TRN during different behavioral states are largely unknown. TRN cells are densely interconnected by electrical synapses. Here we show that activation of the persistent sodium current (INaP) by depolarization causes up to four-fold changes in electrical synaptic efficacy between TRN neurons. We further show that amplification of electrical synaptic responses strongly enhances tonic spike synchrony but, surprisingly, does not affect burst coordination. We use a Hodgkin-Huxley model to gain insight into the differences between the effects of burstlets, spikelets and amplification on burst and spike times.